KIRKPATRICK MODEL EVALUATION ON THE IMPLEMENTATION OF STRENGTHENING SCHOOL SUPERVISORS BASED ON BEST PRACTICE, HOTS AND ADULT LEARNING - Renny Yunus; Nirva Diana; Siti Patimah; Agus Pahrudin (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
Evaluation is a process or activity of selecting, collecting, analyzing and presenting information that can be used as a basis for decision making and for the preparation of further programs. Petronila Jean describes that education and training is the method of technical and vocational education and training which is appreciated as an effort to acquire practical skills, attitudes, understanding and being able to process them in Best Practice and generate an idea or idea about a technique, method, process, activity. , intensive so as to provide them with new knowledge and implications. This study aims to analyze and find outResult Evaluation on the implementation of training to strengthen school supervisors based on Best Practice, HOTS and adult learning. This research method uses qualitative methods with a sample of 100 school supervisors. The data in this study were collected using a questionnaire and reliability testing was carried out with Cronbach Alpha. The results of the study describe the Kirkpatrick Evaluation Model in the Training Program for strengthening school supervisorsThe results of the learning outcomes of the training participants have increased and the difference is significant, it's just that when viewed from each aspect, namely aspects of knowledge, understanding and application, that the results obtained have increased but the results of the differences and the improvements are not significant.